2018
DOI: 10.1111/edt.12445
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term retention of avulsed maxillary permanent incisors replanted after prolonged non‐physiological storage

Abstract: Ankylosis and external replacement resorption (ERR) are two typical biological responses to delayed replantation of avulsed teeth in cases where adequate root canal treatment is performed. The patient's growth stage affects the progression of root resorption and the long‐term outcome of the affected teeth. This case report describes the long‐term outcome of an 18.5‐year‐old patient following an accident in which both of his maxillary central incisors were avulsed and replanted after four hours of non‐physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 33 publications
1
23
0
1
Order By: Relevance
“…An unfavourable outcome after replantation does not mean that replantation should not be done. Even if a tooth is ankylosed, it may remain in place for several decades in adult patients and preserve the alveolar bone . In young patients, if ankylosis occurs, the replacement resorption tends to evolve more rapidly .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unfavourable outcome after replantation does not mean that replantation should not be done. Even if a tooth is ankylosed, it may remain in place for several decades in adult patients and preserve the alveolar bone . In young patients, if ankylosis occurs, the replacement resorption tends to evolve more rapidly .…”
Section: Discussionmentioning
confidence: 99%
“…Even if a tooth is ankylosed, it may remain in place for several decades in adult patients and preserve the alveolar bone. 11,34 In young patients, if ankylosis occurs, the replacement resorption tends to evolve more rapidly. 11,22 There is also a risk that the replanted tooth may become infra-positioned, inhibiting the growth of the related alveolar bone process.…”
Section: Discussionmentioning
confidence: 99%
“…For an avulsed tooth with closed apices, it is recommended that if replanted, the tooth undergoes elective root canal treatment [1][2][3][4][5]. The tooth is normally splinted with a flexible splint for up to 2 weeks instead of a rigid splint to prevent ankylosis.…”
Section: Introductionmentioning
confidence: 99%
“…Some contraindications for replanting avulsed teeth include a patient who is immunocompromised, deciduous teeth and severe cardiac defects, unrestorable decay, severe uncontrolled diabetes, and severe mental disability. Long-standing, widely regarded guidelines have been available for dealing with dental trauma cases, and there are numerous studies on the outcome of avulsed teeth [1,[3][4][5][6][7][8][9]. There is however a scarcity of studies which describe the outcome of replanted closed-apex permanent teeth which have not undergone root canal treatment (RCT)-such as abscess formation, discoloration, and tooth loss.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity in treatment of avulsion treatment resides in readiness of the replantation procedure, which is stated to be in the range of 1 to 4 hours after avulsion (1,5,6), the longer it takes the less the chances of survival of the tissues of retaining vitality , and the slimmer the chances of a successful replantation procedure (7)(8)(9)(10); studies have shown that the best possible prognosis is replantation within 5 minutes (11), and the storage of the avulsed tooth in a suitable storage medium, such as, salt solution, coconut water, milk, saliva, calcitonin and alendronate. Thus the treatment plan must take into account the time and storage medium of the avulsed tooth, as well as the age of the patient and the post-implantation care (1).…”
Section: Introductionmentioning
confidence: 99%